Capital structure: focus on plantation listed companies in Malaysia / Muhammad Zulhamizan Zulkarnain - Zulkarnain, Muhammad Zulhamizan (2018)
Capital structure is the way a firm finances its asset through the consolidation of debt, equity or hybrid securities. The purpose of this study is to identify the capital structure volatility by measuring their debt volatility on six plantation companies in Malaysia between 2008 until 2017. Prior study found that company with the high debt ratio will lead to be smaller and were less profitable. Therefore, evaluating the factor that influence firm leverage and recognition of the sources of difference in company-level profitability has been consider as key research subjects. The independent variables for this study consists of firm size, return on asset, revenue growth and dependent variable in this study is debt ratio. The data collection from six companies in plantation sector that listed on Bursa Malaysia Berhad for ten years using financial statement from the annual report of every company. The data were analysed by using Pooled Ordinary Least Square (Pooled OLS) to evaluate the relationships between the variables by Eviews 9. This study expected to find the independent variables are positively significant relationship to the company's debt ratio.